A evasão de alunos do curso de física do Campus de Guaratinguetá da UNESP - Rabelo, Leandro de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The objective the work at hand has is to discuss the dropouts of students from the major Physics in the campus of Guaratinguetá – UNESP. A survey has been made about the number of graduated and evaded students of each class since 1989, year that this course was created, until the year 2011. For this purpose, lists were collected from the section of graduation of the university, in which you will find names, year of entry, way of entry and situation of each students already enrolled in the course. Data about the dropouts of other courses of Physics at UNESP were also collected, in order to compare with the results from the unity of Guaratinguetá. Besides that, the results from researches about the lack of physics professors in the country were also taken into consideration. Some of this research sought to identify the main reasons of dropouts from the students of Physics. The data collected indicates that the dropout of this course in the campus of Guaratinguetá is higher when compared to the dropouts of others in this institution. It’s also true that the dropout rates haven’t changed significantly over the years, the average being 66.2% in the period between 1989 and 2007. However, the reason for the dropouts has changed of the years, dropouts to change for other majors increased, especially after 2005, being responsible for almost half of the dropouts in the last three years. The survey with the enrolled students of 2012 showed that this is a group of young students that don’t work and many of them have enrolled with the intension to transfer to other courses. These data contradicts the results of some researches that point out difficulties for students to reconciling work with study as one of the main causes of the dropouts. This suggests the picture in this work about the dropouts... (Complete abstract click electronic access below)

O presente trabalho tem como objetivo discutir a evasão no curso de Física do campus de Guaratinguetá da UNESP. Foi realizado um levantamento do número de alunos formados e evadidos de cada turma desde 1989, ano da abertura do curso, até o ano de 2011. Para isso foram coletadas listas junto à seção de graduação da unidade universitária nas quais consta o nome, ano de ingresso, forma de ingresso e a situação atual de cada aluno já matriculado no curso. Esses dados foram tabulados e apresentados em tabelas e gráficos. Por meio de um questionário buscou-se identificar o perfil dos alunos ingressos no ano de 2012 e indícios de intencionalidade de abandonar o curso. Também se levantaram dados de evasão de outros cursos de Física da UNESP, visando comparar com aqueles do curso de Guaratinguetá. Além disso, estudaram-se resultados de pesquisas sobre a falta de professores de Física no país e sobre motivos da evasão em cursos de Física. Os dados indicam que a evasão no curso de Física do campus de Guaratinguetá da UNESP é alta quando comparada à evasão em outros cursos de Física da mesma universidade. Também se percebe que os índices de evasão não se alteraram de maneira significativa ao longo dos anos, sendo em média 66,2% no período entre os anos de 1989 a 2007. No entanto, a forma de abandono do curso mudou ao longo dos anos, a evasão por transferência para outros cursos aumentou, principalmente depois de 2005, sendo responsável por quase a metade dos abandonos dos ingressos nos últimos três anos. A pesquisa realizada com os alunos ingressantes em 2012 revelou que muitos já ingressam no curso de Física com o interesse de se transferir para outros cursos e que se trata de uma turma de alunos jovens que não trabalha. Esses dados contrariam resultados de algumas pesquisas sobre evasão nos cursos de Física do país, que apontam como... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Física - Estudo e ensino; Evasão escolar